2012
DOI: 10.1002/bip.22098
|View full text |Cite
|
Sign up to set email alerts
|

Lipid‐transfer proteins

Abstract: Lipid-transfer proteins (LTPs) are basic proteins found in abundance in higher plants. LTPs play lots of roles in plants such as participation in cutin formation, embryogenesis, defense reactions against phytopathogens, symbiosis, and the adaptation of plants to various environmental conditions. In addition, LTPs from field mustard and Chinese daffodil exhibit antiproliferative activity against human cancer cells. LTPs from chili pepper and coffee manifest inhibitory activity against fungi pathogenic to humans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 92 publications
0
16
0
Order By: Relevance
“…Despite their name, a role in intracellular lipid transport is considered unlikely, based on their extracellular localization. A number of other biological roles, including antimicrobial defence, signaling, and cell wall loosening, have been proposed, but conclusive evidence is generally lacking, and these functions are not well correlated with in vitro activity or structure (Ng et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Despite their name, a role in intracellular lipid transport is considered unlikely, based on their extracellular localization. A number of other biological roles, including antimicrobial defence, signaling, and cell wall loosening, have been proposed, but conclusive evidence is generally lacking, and these functions are not well correlated with in vitro activity or structure (Ng et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier it was reported that Small heat shock proteins (sHSPs) varies from 15–42 kDa [20] that play a significant role in providing resistance to variety of abiotic stresses such as drought, salt, cold and oxidants besides high temperature [21, 22]. Tzi et al [23] reported that DnaJ protein plays an important role in various stress response mechanism. Clement et al [24] reported that DnaJ protein interacts with Hsp70 that might also be involved with ABA signalling.…”
Section: Discussionmentioning
confidence: 99%
“…Many AMPs are cysteine-stabilized and these have been classified into several families [14], including cyclotides [15], defensins [16], hevein-like peptides [17], lipid transfer proteins [18], and snakins [11,19]. The snakin family is a novel plant antimicrobial peptide family which shows good similarity with the members of the gibberellic acid stimulated transcript (GAST) and gibberellic acid stimulated in Arabidopsis (GASA) protein families in Arabidopsis [20].…”
Section: Introductionmentioning
confidence: 99%